Analysis of 21st Century Communication Skills of Elementary School Students - Suryani, Hani; Hendriawan, Deri (Dinasti Publisher, 2025)
This study analyzes the communication skills of elementary school students in the 21st century learning context, where communication is recognized as one of the most essential competencies for academic and social success. The research was conducted with sixth-grade students in a private elementary school in Bandung during the 2023/2024 academic year. This study employed a quantitative descriptive method. Data were collected through a 25-item questionnaire developed from five indicators of communication skills: Respect, Empathy, Audible, Clarity, and Humble. The instrument was tested for validity and reliability, yielding strong results (average r-value = 0.683; Cronbach’s alpha = 0.94). The findings show that most students (40%) are in the medium category, with 25% in the high and very high categories, and 35% in the low and very low categories. These results indicate that while many students possess functional communication skills, a significant portion still faces difficulties in clarity, audibility, and confidence when interacting. The study concludes that systematic and student-centered approaches are required to strengthen communication skills. Strategies such as role-playing, project-based learning, and structured feedback are recommended to support students across different proficiency levels and to foster more effective learning environments.